Interaction between the State and Large Business in the Financial Market and Foreign Economic Activity: Taxation in the Context of Sustainable Development - Slavkova, Alla; Pyslytsia, Anna; Rudyk, Nataliia; Volkovskyi, Ievgen; Kolomiiets, Hanna (Asian Journal of Interdisciplinary Research, 2026)
The paper analyzes the impact of Ukraine’s tax system on the shaping of interaction between the state and large corporations in the financial market and in foreign economic activity. Tax-related incentives and burdens across three export-oriented sectors (energy, agriculture, and manufacturing) that jointly account for more than 70% of Ukraine’s export revenues were defined based on a descriptive analysis of fiscal datasets. The study covered the period from 2015 to 2023. With the help of qualitative content analysis of policy documents and corporate sustainability reports. The study found that enterprises that benefited from preferential measures under the "green" tax invested more in sustainable investments than firms operating under standard taxes. In particular, renewable energy enterprises increased sustainable investments by 340% between 2015 and 2023. The results of the panel regression confirmed that the presence of tax benefits increased the intensity of sustainable investment by 0.7–0.9 percentage points of annual income. However, the effectiveness of tax benefits was limited by regulatory fragmentation, political instability, and geopolitical shocks. The analysis also reveals limited systemic integration of fiscal instruments with the UN Sustainable Development Goals (SDGs), as most tax benefits were sector-specific. Thus, it is proven that Ukraine needs an integrated, time-limited fiscal system that integrates sustainable development goals into tax policy. This involves simplified regulatory roadmaps for green investments and institutionalized mechanisms for dialogue between the state and big business.